2016
DOI: 10.1177/0031512516647802
|View full text |Cite
|
Sign up to set email alerts
|

Does Exercise Reduce Aggressive Feelings? An Experiment Examining the Influence of Movement Type and Social Task Conditions on Testiness and Anger Reduction

Abstract: In the present study, it was assumed that a decrease in aggressive feelings is stronger with movements that are unlike aggressive actions compared with those that are similar to aggressive actions. Furthermore, cooperative exercise tasks were expected to lead to lower aggressive feelings compared with competitive tasks. After undergoing an induction of aggressive feelings, 60 participants were randomly assigned to one of six experimental treatment groups, each differing in "movement type" (rowing and combat ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 34 publications
0
9
0
3
Order By: Relevance
“…Dies entspricht einem Vorgehen, das bereits in vorherigen Untersuchungen bewährt angewendet worden ist (vgl. [11,16]).…”
Section: Messinstrumenteunclassified
See 1 more Smart Citation
“…Dies entspricht einem Vorgehen, das bereits in vorherigen Untersuchungen bewährt angewendet worden ist (vgl. [11,16]).…”
Section: Messinstrumenteunclassified
“…Kooperative Angebote, wie beispielsweise aerobes Tanztraining, reduzieren aggressive Gefühle effektiver als kompetitive Angebote, wie beispielsweise ein Basketballspiel [9,10]. Ähnliche Hinweise auf die Relevanz von sozialen Aufgabenbedingungen ergeben sich aus einem Laborexperiment [11]. Empirisch immer noch unbeantwortet bleibt jedoch die Frage nach dem Mechanismus, weshalb die sozialen Aufgabenbedingungen unterschiedlich wirken.…”
Section: Introductionunclassified
“…Anger and excessive physical activity increase the risk of the heart attack (Smyth et el., 2016) and it can be presumed that the combination of these two factors will make the risk even higher. The study by Pels et al, (2016) was related to anger. These authors found that non-aggressive physical activity, it was rowing in their experiment, reduced anger, but practicing martial arts had no such effect.…”
Section: Physical Activity and Angermentioning
confidence: 99%
“…Yapılan çalışmalarda, serbest zaman çerçevesinde odaklanılması gereken bir diğer noktanın da bireylerin yetkinlik algıları olduğu söylenmektedir (Demirel vd., 2017;Koçak, 2017;Pels ve Kleinert, 2016a;2016b;Sarol ve Çimen, 2017). Bu noktadan hareketle, kişinin belirli bir sosyal görevle ilgili sergilemiş olduğu performansı hakkındaki hüküm ve değerlendirmeleri (Gresham vd., 2001) olarak tanımlanan sosyal yetkinlik kavramı önemli bir odak noktası olarak dikkat çekmektedir.…”
Section: Introductionunclassified